2006
DOI: 10.1128/mcb.26.1.155-168.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Forkhead Transcription Factor FoxI1 Remains Bound to Condensed Mitotic Chromosomes and Stably Remodels Chromatin Structure

Abstract: All forkhead (Fox) proteins contain a highly conserved DNA binding domain whose structure is remarkably similar to the winged-helix structures of histones H1 and H5. Little is known about Fox protein binding in the context of higher-order chromatin structure in living cells. We created a stable cell line expressing FoxI1-green fluorescent protein (GFP) or FoxI1-V5 fusion proteins under control of the reverse tetracycline-controlled transactivator doxycycline inducible system and found that unlike most transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 77 publications
(91 reference statements)
4
71
0
1
Order By: Relevance
“…By promoting otic fate in response to Fgf signaling, Foxi1 in the preotic region of wild-type embryos and expanded Foxi1 expression in RAtreated embryos might be involved in lens fate repression. Consistent with this interpretation, microarray analysis covering approximately 20,000 zebrafish genes showed that only seven genes, including pax6b, are significantly repressed after overexpression of Foxi1 (Yan et al, 2006). However, it is also likely that the reduction or loss of lens tissue is not due to misexpression of foxi1 or to a posteriorization of the preplacodal domain, but rather due to the ectopic expression of pax8.…”
Section: Wnt Signaling During Otic Inductionsupporting
confidence: 50%
“…By promoting otic fate in response to Fgf signaling, Foxi1 in the preotic region of wild-type embryos and expanded Foxi1 expression in RAtreated embryos might be involved in lens fate repression. Consistent with this interpretation, microarray analysis covering approximately 20,000 zebrafish genes showed that only seven genes, including pax6b, are significantly repressed after overexpression of Foxi1 (Yan et al, 2006). However, it is also likely that the reduction or loss of lens tissue is not due to misexpression of foxi1 or to a posteriorization of the preplacodal domain, but rather due to the ectopic expression of pax8.…”
Section: Wnt Signaling During Otic Inductionsupporting
confidence: 50%
“…Although many components of both PcG and TrxG proteins have been characterized, yet their relationship with other chromatin-remodeling factors remains to be elucidated. Forkhead transcription factor, Foxi1, stably binds to chromatin through the cell cycle and generally inhibits the accessibility of nucleases to chromatin (Yan et al, 2006b). Given that a cascade of Fox factors have been found to endow progenitor cells with the competence to activate genes in response to tissue-inductive signals (Zaret et al, 2008), an attractive possibility is that the pioneer Fox proteins may be involved in PcG/TrxG complex-mediated chromatin modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Linker histone H1 can serve as a marker of excised chromatin (29,32). Linker histone H1 proteins released after MNase digestion were readily identified in the chromatin released from FOXP3-transfected Jurkat T cells (Fig.…”
Section: Tgf-␤ Treatment Increases the Level Of Acetylated Foxp3 Bounmentioning
confidence: 99%